Patterned Microstructure Fabrication: Polyelectrolyte Complexes vs Polyelectrolyte Multilayers - Gai M. Meiyu; Frueh J. С. Johannes Christoph; Kudryavtseva V. L. Valeriya Lvovna; Mao R. Rui; Kiryukhin M. V. Maxim; Sukhorukov G. V. Gleb Borisovich (2016, 2016)
Title screen